Kształtowanie narodowej wspólnoty w świetle XVI-wiecznego piśmiennictwa historiograficznego. Rekonesans - Hawrysz, Magdalena (Acta Universitatis Lodziensis. Folia Linguistica, 2014)
The paper constitutes an element of a large scale project whose aim consists in the reconstruction of the identity discourse of the First Republic of Poland in historiographic writing. The sketch presents selected linguistic and extra-linguistic mechanism used in historiography for the purpose of developing national community (at that time understood as the nation of the gentry) and strengthening its internal bonds. The mechanisms used to be referred to as cognitive or visual propaganda. The goal of the paper is achieved by means of the presentation of the linguistic means used for the purpose of shaping historical consciousness as the foundation of national community or expressions referring to the basic concepts related to the national community, i.e. names of the country (kingdom, crown, homeland, state, Poland, republic, the Sarmatia), citizens (Polanie, Polacy, Lechy, Lachy, the Sarmatians) and finally – indication of the role of the graphic code. The source documentation includes 16th century Polish language catalogues of monarchs treated as a tool of social communication and the strategic element of state policy.